Unilateral Ureteric Endometriosis at the Pelvic Brim Resulting in Complete Loss of Renal Function - Keisuke Tanaka; Akwasi A. Amoako; Katherine Gray; David Baartz (Hindawi Limited, 2019)
Deep infiltrating endometriosis of the urinary tract is rare but can result in ureteric obstruction, hydroureteronephrosis and renal failure. Ureteric endometriosis usually affects the distal third of the left ureter among women of reproductive age. Greater awareness of ureteric endometriosis and a multidisciplinary approach in the management is essential to achieve optimal outcomes. We present an atypical case of right ureteric obstruction due to endometriosis at the pelvic brim resulting in complete loss of renal function and necessitating nephroureterectomy.